2008
DOI: 10.1074/jbc.m707108200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Binds to the Extracellular Cysteine-rich Domain of Frizzled and Inhibits Wnt/β-Catenin Signaling

Abstract: The amyloid-␤ peptide (A␤) plays a major role in neuronal dysfunction and neurotoxicity in Alzheimer disease. However, the signal transduction mechanisms involved in A␤-induced neuronal dysfunction remain to be fully elucidated. A major current unknown is the identity of the protein receptor(s) involved in neuronal A␤ binding. Using phage display of peptide libraries, we have identified a number of peptides that bind A␤ and are homologous to neuronal receptors putatively involved in A␤ interactions. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(178 citation statements)
references
References 42 publications
2
170
0
1
Order By: Relevance
“…Wnt signaling regulates a variety of critical biological processes, including development, cell movement, cell polarity, axon guidance, and synapse formation [50]. Magdesian and colleagues concluded that A␤ oligomers bind to Fz receptors, producing the inhibition of Wnt signaling, which causes tau phosphorylation and neurofibrillary tangles; that suggests a Wnt/␤-catenin toxicity pathway [48].…”
Section: R Kayed and Ca Lasagna-reeves / Amyloid-β Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling regulates a variety of critical biological processes, including development, cell movement, cell polarity, axon guidance, and synapse formation [50]. Magdesian and colleagues concluded that A␤ oligomers bind to Fz receptors, producing the inhibition of Wnt signaling, which causes tau phosphorylation and neurofibrillary tangles; that suggests a Wnt/␤-catenin toxicity pathway [48].…”
Section: R Kayed and Ca Lasagna-reeves / Amyloid-β Toxicitymentioning
confidence: 99%
“…Magdesian et al showed that A␤ oligomers bind to the Frizzled (Fz) cysteine-rich domain at or in close proximity to the Wnt-binding site and inhibit the canonical Wnt signaling pathway [48]. Wnts are secreted glycoproteins that bind to and signal through Fz receptors and mediate cell-cell communication [49].…”
Section: R Kayed and Ca Lasagna-reeves / Amyloid-β Toxicitymentioning
confidence: 99%
“…But previous studies have shown that A␤ can bind to several members of the frizzled receptor family, acting as an antagonist of Wnts (Magdesian et al, 2008), and that A␤ can lead to upregulation of the Wnt/␤-catenin signaling inhibitor Dickkopf1 (Krupnik et al, 1999). Such interference at the level of the frizzled receptor and the subsequent reduction of the downstream effector ␤-catenin could lead to downregulation of proneural bHLH factors, which are direct targets of Wnt/␤-catenin signaling during cortical development (Hirabayashi et al, 2004).…”
Section: Review Of He and Shenmentioning
confidence: 99%
“…Additionally, Aβ interacts with the α7 nicotinic acetylcholine receptor, promoting the internalization of receptors and the accumulation of intracellular Aβ [147]. Studies have also showed that Aβ interaction to the Frizzled (Fz) receptor inhibit Wnt signaling, resulting in downstream processes causing tau phosphorylation and formation of NFTs [148]. These are a few examples of Aβ interactions with receptors, and the sometimes contradictory reports regarding Aβ interactions might be because different Aβ assemblies or conformations have different targets.…”
Section: Receptor and Membrane Mediated Toxicitymentioning
confidence: 99%